2021
DOI: 10.51910/ijhdr.v9i33.410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biotherapic of Alternaria solani on the early blight of tomato-plant and the in vitro development of the fungus

Abstract: Background: homeopathy is a means permitted in organic agriculture to control disease and plagues; biotherapics are a practical means for farmers to intervene on the health of plants in agro-ecological systems of production. Tomato-plants can be affected by several diseases, one of the most significant ones in Brazil is early blight, caused by fungus Alternaria solani, due to the damage it causes and its wide distribution in the country. Aims: to establish whether a biotherapic of A. solani may interfere on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Early blight is a disease caused by Alternaria solani, which seriously affects tomatoes and other solanaceous plants. 98 It can cause defoliation of plants in leaves and necrosis of stems and fruits in serious cases, leading to plant death. 99 Quiterio-Gutieŕrez et al 100 applied nanoselenium and nanocopper (10 mg/L SeNPs + 50 mg/L CuNPs) to treat tomato early blight, and the results showed that the severity of the tomato infected with bacteria was reduced by 6%.…”
Section: Application Of Nanoselenium In Poultry and Livestockmentioning
confidence: 99%
See 1 more Smart Citation
“…Early blight is a disease caused by Alternaria solani, which seriously affects tomatoes and other solanaceous plants. 98 It can cause defoliation of plants in leaves and necrosis of stems and fruits in serious cases, leading to plant death. 99 Quiterio-Gutieŕrez et al 100 applied nanoselenium and nanocopper (10 mg/L SeNPs + 50 mg/L CuNPs) to treat tomato early blight, and the results showed that the severity of the tomato infected with bacteria was reduced by 6%.…”
Section: Application Of Nanoselenium In Poultry and Livestockmentioning
confidence: 99%
“…In addition, SeNPs can maintain the composition and integrity of the thylakoid membrane. Early blight is a disease caused by Alternaria solani, which seriously affects tomatoes and other solanaceous plants . It can cause defoliation of plants in leaves and necrosis of stems and fruits in serious cases, leading to plant death .…”
Section: Application Of Nanoselenium In Food and Food-related Fieldsmentioning
confidence: 99%
“…Alternaria leaf blight is an important disease of tropical and sub-tropical areas (Yashwant et al, 2017). Alternaria solani usually infect solanaceous crops including potato, tomato, eggplant and pepper (Carneiro et al, 2010).This fungus causes infection on leaves, stem, petiole, twig and fruits as well as leads to the defoliation, drying of twigs and premature fruit drop which ultimately reduce the yield 30 to 65 % in various states (Basu, 1974;Datar and Mayee, 1981;Kamble et al, 2009;Saha and Das, 2013). The disease, if favored by high temperature and humidity (crowded plantation, high rainfall and extended period of leaf wetness from dew) and plants are more susceptible to the blight infection during fruiting period (Momel and Pemezny, 2006).…”
Section: Introductionmentioning
confidence: 99%